Phospholipid Screening Postcardiac Arrest Detects Decreased Plasma Lysophosphatidylcholine: Supplementation as a New Therapeutic Approach - Nishikimi, Mitsuaki; Yagi, Tsukasa; Shoaib, Muhammad; Takegawa, Ryosuke; Rasul, Rehana; Hayashida, Kei; Okuma, Yu; Yin, Tai; Choudhary, Rishabh C; Becker, Lance B; Kim, Junhwan (Critical care medicine, 2022)
Cardiac arrest and subsequent resuscitation have been shown to deplete plasma phospholipids. This depletion of phospholipids in circulating plasma may contribute to organ damage postresuscitation. Our aim was to identify the diminishment of essential phospholipids in postresuscitation plasma and develop a novel therapeutic approach of supplementing these depleted phospholipids that are required to prevent organ dysfunction postcardiac arrest, which may lead to improved survival. Clinical case control study followed by translational laboratory study. Research institution. Adult cardiac arrest patients and male Sprague-Dawley rats. Resuscitated rats after 10-minute asphyxial cardiac arrest were randomized to be treated with lysophosphatidylcholine specie or vehicle. We first performed a phospholipid survey on human cardiac arrest and control plasma. Using mass spectrometry analysis followed by multivariable regression analyses, we found that plasma lysophosphatidylcholine levels were an independent discriminator of cardiac arrest. We also found that decreased plasma lysophosphatidylcholine was associated with poor patient outcomes. A similar association was observed in our rat model, with significantly greater depletion of plasma lysophosphatidylcholine with increased cardiac arrest time, suggesting an association of lysophosphatidylcholine levels with injury severity. Using a 10-minute cardiac arrest rat model, we tested supplementation of depleted lysophosphatidylcholine species, lysophosphatidylcholine(18:1), and lysophosphatidylcholine(22:6), which resulted in significantly increased survival compared with control. Furthermore, the survived rats treated with these lysophosphatidylcholine species exhibited significantly improved brain function. However, supplementing lysophosphatidylcholine(18:0), which did not decrease in the plasma after 10-minute cardiac arrest, had no beneficial effect. Our data suggest that decreased plasma lysophosphatidylcholine is a major contributor to mortality and brain damage postcardiac arrest, and its supplementation may be a novel therapeutic approach.